Transcatheter Arterial Embolization for Intra-abdominal Bleeding - Gill, Stephen D.; Dawson, Stephanie; Kenworthy, Jessie-Anne; Greenhalgh, Jarrod; Hely, Andrew; Harrison, Benjamin; Landers, Steve (Journal of Clinical Interventional Radiology ISVIR, 2019)
Purpose Transcatheter arterial embolization (TAE) is increasingly used for managing hemorrhage. The evidence-base supporting the procedure is accumulating. This study investigated the safety and effectiveness of TAE for intra-abdominal bleeding at a large regional public health service in Australia.Materials and Methods Medical records of all patients undergoing TAE for intra-abdominal bleeding over a 7-year period were retrospectively reviewed, excluding gastric bleeding. Data were extracted into a standardized electronic data collection tool. Technical success of TAE was defined as cessation of active contrast media extravasation on post-procedure angiography. Complications were categorized as intra- and post-procedure. The severity of complications was rated according to the Society of Interventional Radiology Standards of Practice Committee Classifications of Complications by Outcome.Results Ninety-two cases were identified. TAE was technically successful in 70 (94.6%) of the 74 cases when visible contrast media extravasation was evident during angiograph. During procedures, six minor complications occurred such as transient symptomatic hypotension or moderate to severe abdominal pain. Following procedures, eight minor complications were reported: seven cases of hematoma at the catheter access point and one case of contrast reaction. One major complication, bowel ischemia requiring hemicolectomy, occurred post-TAE for a bleeding cecal aneurysm; however, widespread arterial spasm was noted on angiography prior to TAE and interventional colonoscopy had occurred 2 days prior to TAE, suggesting that ischemia was not primarily due to TAE.Conclusion This study supports the use of TAE for a diverse range of cases of intra-abdominal bleeding. TAE produced high rates of complete hemostasis with few complications.
Keywords: embolization; abdomen/gastrointestinal; hemorrhage